International Alliance of Urolithiasis Guideline on Shockwave Lithotripsy - Zeng, Guohua; Zhong, Wen; Chaussy, Christian G; Tiselius, Hans Göran; Xu, Changbao; Turney, Ben; Turk, Christian; Tailly, Geert G; Preminger, Glenn M; Akpinar, Haluk; Petrik, Ales; Bernardo, Norberto; et al. (European urology focus, 2023)
Different international associations have proposed their own guidelines on urolithiasis. However, the focus is primarily on an overview of the principles of urolithiasis management rather than step-by-step technical details for the procedure. The International Alliance of Urolithiasis (IAU) is releasing a series of guidelines on the management of urolithiasis. The current guideline on shockwave lithotripsy (SWL) is the third in the IAU guidelines series and provides a clinical framework for urologists and technicians performing SWL. A total of 49 recommendations are summarized and graded, covering the following aspects: indications and contraindications; preoperative patient evaluation; preoperative medication; prestenting; intraoperative analgesia or anesthesia; intraoperative position; stone localization and monitoring; machine and energy settings; intraoperative lithotripsy strategies; auxiliary therapy following SWL; evaluation of stone clearance; complications; and quality of life. The recommendations, tips, and tricks regarding SWL procedures summarized here provide important and necessary guidance for urologists along with technicians performing SWL. PATIENT SUMMARY: For kidney and urinary stones of less than 20 mm in size, shockwave lithotripsy (SWL) is an approach in which the stone is treated with shockwaves applied to the skin, without the need for surgery. Our recommendations on technical aspects of the procedure provide guidance for urologists and technicians performing SWL.
Keywords: močové kameny; Urinary Calculi; Urolithiasis; litotripse; Lithotripsy; Kidney; Humans; urolitiáza; lidé; Quality of Life; kvalita života; ledviny